Fat grafting: Lipofragmentation X Liposuction - Flavio Henrique Mendes; Fausto Viterbo; Elenice Deffune; Maria Aparecida Custódio Domingues; Marjorie Assis Golim; José Marcos Gabas; Renan Roldi Rossoni;; Helga Caputo Nunes (Revista Brasileira de Cirurgia Plástica)
Introduction: Aiming to obtain autogenous and injectable lipografts from resected tissues in dermolipectomies, this study proposes a new method for harvesting and processing adipose tissue through a specific fragmenting device. The main objective was to establish a comparative analysis of the quality and viability characteristics of the new lipofragmentation technique and those of the well-known liposuction technique, widely accepted as a viable source of fat grafting. In vivo and in vitro assays were designed to evaluate the biological behavior of the samples to guide new and possible human studies with clinical applications. Methods: A post-bariatric patient who underwent abdominal dermolipectomy had her surgical specimen resected, which was divided into four parts that underwent liposuction and lipofragmentation, with and without prior infiltration. All samples were centrifuged and distributed for assays with assessments involving histological analysis, immunohistochemistry, flow cytometry, cell culture, and xenograft injection on the back of 10 Wistar rats, which was evaluated after six weeks for mass, volume, and histological features. Results: The structural characteristics and biological behaviors of fragmented, dry, and infiltrated fat samples were similar to those of liposuction samples. Conclusions: Fat fragmentation transformed the subcutaneous cellular tissue of dermolipectomies into a new, viable injectable lipograft variant, with biological characteristics similar to those of traditional liposuction. Although still preliminary, our results support further investigations to optimize the technique and improve fat grafting and its possible applications in regenerative medicine.